Report 9: Job Evaluation Practices, Proceedings of a Conference, July 1951 - Chartier, Roger (Relations industrielles / Industrial Relations, 1953)
The article briefly reviews "Report 9: Job Evaluation Practices, Proceedings of a Conference," July 1951 (67 pages).